Virtual training: Three tips, three cons and three pros of online fitness training - Kashubara, K. (Track Coach, 2020)
The pandemic has shut down schools, gyms, tracks, and even parks. This environment makes it difficult for athletes to properly train and for coaches to teach. No one knows when the crisis our world is facing will end. What we should know is that the future is now; and that it is time to prepare for a new normal. Part of that normal will be less physical interaction and more virtual.